ASSESSMENT OF THE EFFECT OF MATERNAL PRE-PREGNANCY BODY MASS INDEX ON PREGNANCY OUTCOMES: Pharmaceutical Science-Pharmacy Practice - VAFAEEROK, DR.HEDIEH; RANI.R. HIREMATH, DR.SHOBHA; KAZIM SHERIFF, DR.MOHAMMED; GUDI, DR.SHOBHA (International Journal of Life Science and Pharma Research, 2019)
Obesity is a significant health problem which can lead to serious health complications. It does not exclude pregnant population. It is well known that maternal pre pregnancy obesity and overweight is a common health problem which can lead to adverse neonatal and maternal outcomes such as gestational diabetes, pre eclapmsia, post partum haemorrhage, caesarean delivery, neonatal intensive care unit admission, small/ large for gestational age, stillbirth, etc. The aim of the present study is to assess the effect of maternal pre- pregnancy BMI on maternal and fetal outcomes. It was a prospective hospital based cohort study that was carried out for a period of 6 months at St. Philomena’s Hospital, Bangalore. The subjects were included after obtaining informed consent. Women with multiple pregnancies and pregnant women whose gestational period was<20 weeks and those who were not willing to participate in the study were excluded. All the relevant data of both maternal and fetal demographic details, type of delivery and neonatal outcomes were collected. Chi square test was used to assess associations between maternal BMI and period of gestation, fetal position, type of delivery, fetal weight, newborn complications and Apgar score. A total of 432 pregnant women were included in the study comprising 49.5% normal weight, 29.3% overweight and 21.2% obese women. We observed higher incidence of LSCS and neonatal complications including pneumonia, hydronephrosis, hypoglycaemia, respiratory distress syndrome, transient tachypnea of newborn in obese and overweight mothers compared to normal weight mothers. We could not find any significant relation between pre pregnancy BMI and neonatal birth weight, period of gestation, Apgar score and fetal position at time of delivery. Maternal and neonatal complications are associated with pre pregnancy obesity.